Upaya Peningkatan Hasil Belajar Passing Kaki Bagian Dalam Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw Berbasis Lesson Study Dalam Permainan Sepak Bola Pada Siswi Kelas XI SMK Sultan Agung 2 Tebuireng Jombang Tahun Pelajaran 2014/2015 - Sudrajat, Edo Bagus (STKIP PGRI Jombang, 2013)
the increase in the percentage of students passing judging of learning outcomes using the foot part in the game of football preliminary data for the product of 65% and the process by 60%. In the first cycle judging the percentage of passing students learning outcomes increased by 11%, ie to 76% and the increase of 17% to 77%. And the second cycle percentage of product yields increased again by 9% to 85% and increased the 12% to 89%. Then the quality of learning outcomes with the application of Jigsaw cooperative Lesson Study based on passing the material using the foot part in the game of football showed an increase in the percentage of each is the product of learning by 20% and 29% in the process.